Enlisting rangers and scouts for reconnaissance and surveillance. - Rybski, P.E (IEEE Robotics and automation magazine)
Reconnaissance and surveillance are important activities for both military and civilian organizations, for hostage and survivor rescue, drug raids, response to chemical or toxic waste spills etc. We have developed a distributed heterogeneous robotic team that is based mainly on a miniature robotic system. Because some operations require covert action, most of the robots are extremely small. This also allows them to be easily transported and allows for a greater number to be brought into use for a single operation. This makes them expendable without jeopardizing the overall mission. We call these small robots scouts. Their individual components must all be exceedingly small, and their overall design must make maximum use of all available space. They must make efficient use of resources (e.g., batteries). We meet these challenges with an innovative design and creative use of additional support. We team the scouts with larger ranger robots, which can transport the scouts over distances of several kilometers, deploy them rapidly over a large area, coordinate their behavior, and collect and present the resulting data. We present the scouts and rangers, discuss their capabilities along with the associated software, and describe demonstrations conducted to test the innovative aspects of the system. We also discuss related work, analyze our results, and draw conclusions